Analisis Bottleneck Produksi Akibat Material Berkarat Menggunakan Metode Theory of Constraints pada Workshop 2 PT. Triangle Motorindo - Ilham Amri Yafi; Nurwidiana Nurwidiana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze production bottlenecks caused by rusty materials using the Theory of Constraints approach at Workshop 2 of PT. Triangle Motorindo, which manufactures three-wheeled vehicle frames. The study employs an empirical, case-study-based method through direct observation of the production process, measurement of work time, recording of the quantity of rusty materials, and evaluation of effective production capacity. Data were analyzed using the stages of constraint identification, constraint exploitation, process subordination, constraint elevation, and constraint re-evaluation to determine the impact of rusty materials on production throughput. The results indicate that rusty materials cause an average additional grinding time of 10 minutes per unit, thereby reducing effective production capacity and triggering idle time at the welding, assembly, and painting stations. Total production time loss reached 260 minutes with a decrease in output of 30 units during the observation period. The implementation of a constraint elevation strategy through the addition of grinding machines, the allocation of dedicated operators, and the use of rust-resistant materials successfully reduced backlogged units to 5 units per week and increased daily output efficiency to over 95%. The research findings underscore the importance of material quality control in maintaining the stability of production flow in metal fabrication-based manufacturing.